Effects of Isometric Plantar-Flexion on the Lower Limb Muscle and Lumbar Tissue Stiffness - Chen, Baizhen; Cui, Shaoyang; Xu, Mingzhu; Zhang, Zhijie; Liu, Chunlong (Frontiers in Bioengineering and Biotechnology, 2022)
Purposes: This study investigated the effects of isometric plantar-flexion against different resistances on the thoracolumbar fascia (TLF), erector spinae (ES) and gastrocnemius stiffness by shear wave elastography (SWE). The purpose was to explore the interaction between the lower limb muscle and lumbar tissue in myofascial tensegrity network. Methods: Twenty healthy young female were recruited in this study. The stiffness of the TLF, ES, medial gastrocnemius (MG) and lateral gastrocnemius (LG) were measured by SWE under four isometric plantar-flexion resistance conditions. The resistance conditions involved 0% maximum voluntary isometric contraction (MVIC), 20% MVIC, 40% MVIC and 60% MVIC. Results: There was a strong correlation between the stiffness change of MG and that of TLF (r=0.768-0.943, p<0.001), ES (r=0.743-0.930, p<0.001), while moderate to strong correlation between MG and that of LG (r=0.588-0.800, p<0.001). There was no significant difference in the stiffness between nondominant and dominant sides of TLF and ES under the resting position(p>0.05). The increase in stiffness of the TLF, ES, MG, LG with MVIC percentage(p<0.05), and the stiffness of TLF and ES on the nondominant side is much higher than that on the dominant side. Conclusions: Our data shows that isometric plantar-flexion has a significant effect on the stiffness of the lumbar soft tissue and gastrocnemius. Gastrocnemius has a strong correlation with the stiffness changes of TLF and ES, which provides preliminary evidence for exploring the myofascial tensegrity network between the dorsal side of lower limb muscle and lumbar tissue.